Exploring the role of IL-1β in inflammatory bowel disease pathogenesis - Aggeletopoulou, Ioanna; Kalafateli, Maria; Tsounis, Efthymios P.; Triantos, Christos (Frontiers in Medicine, 2024)
Interleukin 1β (IL-1β) is a significant mediator of inflammation and tissue damage in IBD. The balance between IL-1β and its endogenous inhibitor-IL-1Ra-, plays a critical role in both initiation and regulation of inflammation. However, the precise role of IL-1β as a causative factor in IBD or simply a consequence of inflammation remains unclear. This review summarizes current knowledge on the molecular and cellular characteristics of IL-1β, describes the existing evidence on the role of this cytokine as a modulator of intestinal homeostasis and an activator of inflammatory responses, and also discusses the role of microRNAs in the regulation of IL-1β-related inflammatory responses in IBD. Current evidence indicates that IL-1β is involved in several aspects during IBD as it greatly contributes to the induction of pro-inflammatory responses through the recruitment and activation of immune cells to the gut mucosa. In parallel, IL-1β is involved in the intestinal barrier disruption and modulates the differentiation and function of T helper (Th) cells by activating the Th17 cell differentiation, known to be involved in the pathogenesis of IBD. Dysbiosis in the gut can also stimulate immune cells to release IL-1β, which, in turn, promotes inflammation. Lastly, increasing evidence pinpoints the central role of miRNAs involvement in IL-1β-related signaling during IBD, particularly in the maintenance of homeostasis within the intestinal epithelium. In conclusion, given the crucial role of IL-1β in the promotion of inflammation and immune responses in IBD, the targeting of this cytokine or its receptors represents a promising therapeutic approach. Further research into the IL-1β-associated post-transcriptional modifications may elucidate the intricate role of this cytokine in immunomodulation.